Soberania nos estados fracassados : o caso da Somália - Emerenciano, Célio Virgínio (2015)
Disciplinary study in the area of Applied Social Sciences, which establishes the relationship between international law and at failed states, developed as Coursework Sovereignty is directly linked to the monopoly of force and is directly linked to the state since its conception to maintenance. The problem we found today is in relation to the capacity of states to use this attribute of power when we look at failed states. This dissertation deals with elements of history, politics and law, in an analysis devoted to the case of failure of the Somali state. The vacuum of power and the resultant anomie of the failure of Somali, tested the international community through the UN and the Commission on Intervention and State Sovereignty, been creating a new concept of sovereignty based on the responsibility of States on the subject. The methodology consists of the survey and reading theoretical texts concerning the object of research.